Laccase-catalysed protein-flavonoid conjugates for flax fibre modification - Kim, S (2012)
The introduction of flavonoid compounds into proteins can improve the natural properties of proteins, being promising products which essentially require antioxidant property. The oxidative conjugation of protein–flavonoids was processed by laccase catalysis resulting in the synthesis of biologically functional polymers. The new reaction products were detected in terms of sodium dodecyl sulfate polyacrylamide gel electrophoresis and matrix-assisted laser desorption/ionisation-time of flight mass spectra, showing a greater molecular weight formation. Their characterisations were further carried out in terms of UV–Vis spectroscopy, photon correlation spectroscopy, differential scanning calorimetry and Fourier transform infrared (FT-IR) spectroscopy analysis. In addition, their application of protein–flavonoid conjugates onto flax fibres was exploited to supplement a suitable microorganism environment of protein-possessed fibres. The anchoring of conjugates onto cationised fibres was successfully performed by ionic interaction with negatively charged proteins. The level of anchoring efficiency was quantified in terms of measuring colour strength (k/s) and fluorescence microscopy analysis. The conjugates onto fibres presented acceptable durability in terms of washing resistance and the surface became hydrophilic when α-casein–catechin was applied (lower contact angle 48°). By the anchoring of protein–flavonoid conjugates onto flax fibres, the final products with new colour generation and antioxidant activity (>93%) were obtained.